Exploratory Analysis of Behavioral Impulsivity, Pro-inflammatory Cytokines, and Resting-State Frontal EEG Activity Associated With Non-suicidal Self-Injury in Patients With Mood Disorder - Kim, Ji Sun; Kang, Eun-Sook; Bahk, Yong Chun; Jang, Sunglee; Hong, Kyung Sue; Baek, Ji Hyun (Frontiers in Psychiatry, 2020)
Introduction: Non-suicidal self-injury (NSSI) is a rapidly increasing mental health problem that requires more clinical attention. In this study, we aimed to explore the biobehavioral markers of NSSI in participants with mood disorders. Methods: A total of 45 participants with mood disorders (bipolar I, II, and major depressive disorder) were included in the study. Behavioral impulsivity was measured using the immediate memory task (IMT)/ delayed memory task (DMT) and the go-no-go (GNG) tests. Plasma levels of tumor necrosis factor- (TNF-), interleukin 1 beta (IL-1), and interleukin 6 (IL-6) and resting-state quantitative electroencephalography (qEEG) were measured. Results: The NSSI group had shorter GNG reaction time (GNG-RT) and higher TNF- levels compared to the non-NSSI group. TNF- was positively correlated with frontal theta power. In addition, GNG-RT showed a significant positive association with frontal alpha activity. Conclusion: NSSI in mood disorders was associated with increased behavioral impulsivity and greater inflammation. Increased pro-inflammatory cytokines were associated with frontal theta power and increased theta-beta ratio. Increased inflammation might change major neurotransmitter metabolism, which eventually affects frontal function and decreases response inhibition. Further studies to explore their causal relationship are warranted.